THE PARTIDO ACCIÓN NACIONAL (PAN) IN THE FIGHT TO NOT DECRIMINALIZE ABORTION IN THE DISTRITO FEDERAL, MEXICO (Andamios, Revista de Investigación Social, 2011)
This work has as aim objective analyze the position that supported the National Action Party in the fight for not authorization of the abortion in the Federal District. As part of a wide network of social actors who demonstrate opposition to the approval of the most recent reforms on that matter, many PAN´s members on the federal government, as legislators and leaders of these party participated on the public dispute on the base of an erroneous conception on the laicism of the Mexican state. The PAN reduced the problematic around the abortion with moralizing theses and it was the catalyst of a new onslaught of the conservative catholics against the laical state.